International Import Competition and the Decision to Migrate: Evidence from Mexico - Kaveh Majlesi; Gaia Narciso (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
We analyze the effects of the increase in China's import competition on Mexican domestic and international migration. We exploit the variation in exposure to competition from China, following its accession to the WTO in 2001, across Mexican municipalities and estimate the effect of international competition on the individual decision to migrate. Controlling for individual and municipality features, we find that individuals living in municipalities more exposed to Chinese import competition are more likely to migrate to other municipalities within Mexico, while a negative effect is found on the decision to migrate to the US. In particular, we find that Chinese import competition reduces migrants' negative self-selection: the rising international competition lowers the likelihood of low-educated, low-income people to migrate to the US, by making them more financially constrained.
Keywords: 330